Tips and tricks of the propensity score methods in the thoracic surgery research - Bertolaccini, Luca; Pardolesi, Alessandro; Solli, Piergiorgio (Journal of Thoracic Disease, 2017)
Without randomization, the differences in the distribution of baseline covariates can confound the evaluation of outcomes between the groups. To estimate the causal effects of treatment on the results randomized clinical trials (RCT) are routinely used. When RCT are not feasible for cost, time, and ethical issues, the effect of treatment on an inevitable outcome could be investigated by using a non-experimental study design. The propensity score (PS) refers to the individual probability, for a subject involved in a study, of receiving a new treatment rather than the control treatment. PS matching is a valuable and increasingly popular tool for dealing with observational data and non-random treatment assignment. Nevertheless, surgeons need to proceed with caution and apply PS methods appropriately.